KARAKTERISASI MORFOLOGI TANAMAN ANDALIMAN (Zanthoxylum acanthopodium DC.) DI BEBERAPA DESA KECAMATAN DOLOG MASAGAL KABUPATEN SIMALUNGUN - Hutauruk, Sixtus; Purba, Meliani Arnefly; Siregar, Benedicta Lamria (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study aims to identify the morphological characteristics of the types of andaliman plants (Zanthoxylum acanthopodium DC.) in several villages in Dolog Masagal District, Simalungun Regency. This research was conducted in Bittang Village, Tambun Marisi Village, Raya Usang Village, and Gotting Village from February to April 2022. These villages were chosen as research areas because several of these villages are Andaliman producing villages in Dolog Masagal District. This study uses a survey method with the guide of the IPGRI and UPGMA reliable descriptor. The sampling technique was purposive sampling. Parameters observed were plant height, stem circumference, crown shape, stem color, leaf shape, leaf length, leaf width, leaf color, leaf edge, leaf surface, thorn shape, thorn color, thorn length, flower color, flower position, number petals, petal color, anther color, fruit diameter, fruit weight, young fruit color, old fruit color, fruit shape, fruit taste, fruit aroma, number of fruits per bunch, number of seeds, seed shape, seed surface, color young seeds and the color of old seeds. The results showed that Sihorbo's andaliman had distinctive characteristics, namely large fruit, coarse hair on the leaf surface compared to the coarse Simanuk leaf surface, and low production; whereas Simanuk's andaliman has the characteristics of small fruit, sharper taste and aroma than Sihorbo, fruit sticking more to the stem than Sihorbo and high production.